2019
DOI: 10.3390/s19163569
|View full text |Cite
|
Sign up to set email alerts
|

Snow Albedo Seasonality and Trend from MODIS Sensor and Ground Data at Johnsons Glacier, Livingston Island, Maritime Antarctica

Abstract: The aim of this work is to investigate whether snow albedo seasonality and trend under all sky conditions at Johnsons Glacier (Livingston Island, Antarctica) can be tracked using the Moderate Resolution Imaging Spectroradiometer (MODIS) snow albedo daily product MOD10A1. The time span is from December 2006 to February 2015. As the MOD10A1 snow albedo product has never been used in Antarctica before, we also assess the performance for the MOD10A1 cloud mask. The motivation for this work is the need for a descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 61 publications
(91 reference statements)
3
11
0
Order By: Relevance
“…Only these months were selected to avoid biases caused by seasonal variations and also because data availability is highly variable in the remaining months. Although MODIS describes the temporal evolution of the in situ data, a greater dispersion in the satellite data was observed, as already referred to by, among other authors, Stroeve et al [25] for Greenland and Calleja et al [12] for our study area. It has been shown that the best results with MODIS are obtained after the application of filters that correct for the increase in temporal variability with respect to in situ data, described among others by Calleja et al [12], Stroeve et al [25], and Box et al [20].…”
Section: Albedo Trendsupporting
confidence: 74%
See 4 more Smart Citations
“…Only these months were selected to avoid biases caused by seasonal variations and also because data availability is highly variable in the remaining months. Although MODIS describes the temporal evolution of the in situ data, a greater dispersion in the satellite data was observed, as already referred to by, among other authors, Stroeve et al [25] for Greenland and Calleja et al [12] for our study area. It has been shown that the best results with MODIS are obtained after the application of filters that correct for the increase in temporal variability with respect to in situ data, described among others by Calleja et al [12], Stroeve et al [25], and Box et al [20].…”
Section: Albedo Trendsupporting
confidence: 74%
“…Figure 2 shows in situ albedo values, MOD10A1, MYD10A1, and MCD43 (BSA and WSA) for J-F-M. As can be seen, the distribution of the in situ data values is much more homogeneous than in the MODIS products, where extremely low values are observed. An increasing trend in albedo has been documented for the study area in the study period (2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) based on data from MOD10A1 C5 and in situ data [12]. With C6 data, in all cases, there is an increasing trend.…”
Section: Albedo Trendmentioning
confidence: 85%
See 3 more Smart Citations